Analisis Dakwaan atas Tindak Pidana Mendistribusikan Informasi Elektronik yang Melanggar Kesusilaan di Kejaksaan Negeri Padang - Fitria, Wiza; Yustrisia, Lola; Munandar, Syaiful (Universitas Ekasakti, 2023)
State institutions that exercise State power, especially in the field of prosecution, are called the Prosecutor's Office of the Republic of Indonesia. The Prosecutor's Office is a body that has authority in law enforcement and justice, the Prosecutor's Office itself is led by the Attorney General, the High Prosecutor's Office and the District Attorney's Office which is an integral and inseparable whole. The indictment for the Public Prosecutor is the basis for proving Juridical Analysis, filing charges and legal remedies by the prosecutor. The type of research used is empirical juridical, which is research oriented to data collection at the location. As for the results of research on the consideration of the public prosecutor in making charges, the first thing that is done is in terms of case files, case files from investigators that have been declared complete by the investigating prosecutor are poured into the form of P-21. In the sense that the case file is declared complete because it has met the formal and material requirements. The public prosecutor uses the alternative indictment i.e. first, second or third, The alternative indictment is made in the form of an indictment that includes two or more several Articles that are placed the word